Photoacclimation and Light Thresholds for Cold Temperate Seagrasses - Léger-Daigle, Romy; Noisette, Fanny; Bélanger, Simon; Cusson, Mathieu; Nozais, Christian (Frontiers in Plant Science, 2022)
Water quality deterioration is expected to worsen the light conditions in shallow coastal waters with increasing human activities. Temperate seagrasses are known to tolerate a highly fluctuating light environment. However, depending on their ability to adjust to some decline in light conditions, decreases in daily light quantity and quality could affect seagrass physiology, productivity, and eventually survival if the Minimum Quantum Requirements (MQR) are not reached. To better understand if, how, and to what extent photosynthetic adjustments contribute to light acclimation, eelgrass (Zostera marina L.) shoots from the cold temperate St. Lawrence marine estuary (Rimouski, Quebec, Canada) were exposed to seven light intensity treatments (6, 36, 74, 133, 355, 503 and 860 µmol photons m-2 s-1, 14:10 light:dark photoperiod). Photosynthetic capacity and efficiency were quantified after five and 25 days of light exposure by Pulse Amplitude Modulated (PAM) fluorometry to assess the rapid response of the photosynthetic apparatus and its acclimation potential. Photoacclimation was also studied through physiological responses of leaves and shoots (gross and net primary production, pigment content and light absorption). Shoots showed proof of photosynthetic adjustments at irradiances below 200 µmol photons m-2 s-1, which was identified as the threshold between limiting and saturating irradiances. Rapid Light Curves (RLC) and net primary production (NPP) rates revealed sustained maximal photosynthetic rates from the highest light treatments down to 74 µmol photons m-2 s-1, while a compensation point (NPP = 0) of 13.7 µmol photons m-2 s-1 was identified. In addition, an important package effect was observed, since an almost three-fold increase in chlorophyll content in the lowest compared to the highest light treatment did not change the leaves’ light absorption. These results shed new light on photosynthetic and physiological processes triggering light acclimation in cold temperate eelgrass. Our study documents an MQR value for eelgrass in the St. Lawrence estuary, which is highly pertinent in the context of conservation and restoration of eelgrass meadows.